Mekanisme dan Instrumennya Pasar Uang dan Pasar Modal Syariah di Indonesia - Nun Tuhfa (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2017)
In Islamic investment is a muamalah activity is highly recommended, because by investing property owned to be productive and also bring benefits to others. The Qur’an itself strictly prohibits the hoarding activity (iktinaz) against the property owned. (Surah 9:33). To realize the investment call, it must be created a means of investing. Many people choose to invest in the form of investment. One form of investment is to invest his money in the money market and sharia capital markets. With the presence of money market and syariah capital market, providing opportunities for Muslims and non-Muslims who want to invest funds in accordance with the principles of sharia that provide calm and confidence for halal transactions. In order to respond to all matters relating to sharia investment as a result of the rapid development of sharia economy around the world, Jakarta formed the Jakarta Islamic Index (JII) issued by PT Bursa Efek Jakarta on July 3, 2000. A wide range of products are offered in Sharia index in JII and ISSI such as stocks, bonds, Islamic mutual funds, etc.